M Projective Curvature Tensor of Nearly Kahler Manifold (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The geometrical characteristics of one of the NK (′′ Nearly Kahler ′′)manifold structures are provided by M, where M represents for the Nearly kahler manifold, and the MProjective Curvature Tensor In this work, we study the properties of a virtually kahler manifold. Important findings of the study include the following: - It was shown that this tensor had the standard properties of Riemannian curvature symmetry. Projective tensor (M- tensor) components to be calculated for the NK manifold. Links between this manifold's tensor components were created after certain observations were made